International reproducibility of single breathhold T2 MR for cardiac and liver iron assessment among five thalassemia centers - Kirk, Paul; He, Taigang; Anderson, Lisa J.; Roughton, Michael; Tanner, Mark A.; Lam, Wynnie W.M.; Au, Wing Y.; Chu, Winnie C.W.; Chan, Godfrey; Galanello, Renzo; Matta, Gildo; Fogel, Mark; et al. (Journal of magnetic resonance imaging, 2010)
Purpose: To examine the reproducibility of the single breathhold T2* technique from different scanners, after installation of standard methodology in five international centers. Materials and Methods: Up to 10 patients from each center were scanned twice locally for local interstudy reproducibility of heart and liver T2*, and then flown to a central MR facility to be rescanned on a reference scanner for intercenter reproducibility. Interobserver reproducibility for all scans was also assessed. Results: Of the 49 patients scanned, the intercenter reproducibility for T2* was 5.9% for the heart and 5.8% for the liver. Local interstudy reproducibility for T2* was 7.4% for the heart and 4.6% for the liver. Interobserver reproducibility for T2* was 5.4% for the heart and 4.4% for the liver. Conclusion: These data indicate that T2* MR may be developed into a widespread test for tissue siderosis providing that well‐defined and approved imaging and analysis techniques are used. J. Magn. Reson. Imaging 2010;32:315–319. © 2010 Wiley‐Liss, Inc.